Bone Marrow-Derived Mesenchymal Stem Cells Restored High-Fat-Fed Induced Hyperinsulinemia in Rats at Early Stage of Type 2 Diabetes Mellitus. (30th March 2020) - Li, Gongchi; Peng, Han; Qian, Shen; Zou, Xinhua; Du, Ye; Wang, Zhi; Zou, Lijun; Feng, Zibo; Zhang, Jing; Zhu, Youpeng; Liang, Huamin; Li, Binghui
Numerous studies have proposed the transplantation of mesenchymal stem cells (MSCs) in the treatment of typical type 2 diabetes mellitus (T2DM). We aimed to find a new strategy with MSC therapy at an early stage of T2DM to efficiently prevent the progressive deterioration of organic dysfunction. Using the high-fat-fed hyperinsulinemia rat model, we found that before the onset of typical T2DM, bone marrow-derived MSCs (BM-MSCs) significantly attenuated rising insulin with decline in glucose as well as restored lipometabolic disorder and liver dysfunction. BM-MSCs also favored the histological structure recovery and proliferative capacity of pancreatic islet cells. More importantly, BM-MSC administration successfully reversed the abnormal expression of insulin resistance-related proteins including GLUT4, phosphorylated insulin receptor substrate 1, and protein kinase Akt and proinflammatory cytokines IL-6 and TNFα in liver. These findings suggested that MSCs transplantation during hyperinsulinemia could prevent most potential risks of T2DM for patients.